A simple up-scalable thermal treatment method for synthesis of ZnO nanoparticles - Lee, Phin Jit; Saion, Elias; Al-Hada, Naif Mohammed; Soltani, Nayereh (MDPI, 2015)
A simple thermal treatment method, utilizing only zinc nitrate, polyvinyl pyrrolidone (PVP), and deionized water, was used to synthesize ZnO nanoparticles, and their characteristics were investigated by various techniques. The TGA measurement demonstrated that the bulk of the capping agent PVP can be removed at temperatures higher than 500 °C and is consistent with the absence of the majority of PVP absorption peaks in the FT-IR spectra. The formation of almost pure ZnO nanoparticles was established by the presence of single absorption peak in the FT-IR spectra due to being only Zn–O bonds at calcination temperatures of 500 °C and above. The TEM images revealed that the nanoparticles have a spherical shape and the particle size increased from 60.1–83.1 nm with an increase in calcination temperatures from 500–600 °C. The XRD diffraction patterns indicated that the particles are of a wurzite lattice structure. The optical properties were determined by UV-Vis spectrophotometer, and it was found that the band gap of ZnO nanoparticles decreased from 3.249–3.239 eV with an increase in calcination temperature from 500–600 °C.